Rekontekstualisasi Peran Tata Bahasa dalam Akuisisi Bahasa Kedua: Telaah Kritis Teori Monitor Krashen - Hasbi, Anang Fajar; Kasmilah, Nurjannah; Farkhan, Muhammad; Ummah, Vina Navirul (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2025)
This article revisits the role of grammar in second language acquisition through a critical approach to the Monitor Theory developed by Stephen D. Krashen. This theory positions grammar as an aid or monitor in the language learning process, not as the primary focus of acquisition. Using a literature review method, this article analyses Krashen's views and compares them with contemporary theories and empirical findings from experts such as Ellis, Swain, Schmidt, and Lightbown & Spada. The results of the study indicate that although explicit grammar instruction plays a role in improving written accuracy and understanding complex structures, effective language acquisition still depends on exposure to meaningful input (comprehensible input) and the use of language in real communication contexts. Therefore, this article emphasises the importance of a balanced approach between grammar learning and contextual language experience. It is hoped that this article will contribute to the development of a more adaptive language pedagogy that is in line with the needs of today's learners.